Some results of hemosorption columns development and usage in Czechoslovakia - Kálal, J; Tlustáková, M (Biomaterials, artificial cells, and artificial organs, 1988)
Hemoperfusion columns packed with active charcoal and a synthetic resin have been manufactured in Czechoslovakia since 1983. In both cases the sorption packings are coated with a layer of poly(2-hydroxyethyl methacrylate). The columns are manufactured in two sizes: for adults (800 ml) and for children (400 ml). The manufacturer is OPS Kolín: the number of columns manufactured so far is 3400.
Keywords: dospělí; Animals; Bilirubin; Hemoperfusion; dítě; Adult; Československo; Charcoal; lidé; polyvinyly; Polyvinyls; hemoperfuze; počet trombocytů; dřevěné a živočišné uhlí; Materials Testing; Platelet Count; polystyreny; Polystyrenes; testování materiálů; bilirubin; Child; zvířata; porfyrie; Czechoslovakia; Porphyrias; Humans